Effect of solid body aspect ratio on natural convection of nanofluid in a square cavity. (December 2018) - Qasem, S.A.; Sivasankaran, S.; Siri, Z.; Othman, W.A.M.
Abstract: The goal of this numerical study is to understand the free convection flow and transfer of heat in a differentially heated cavity having solid block in the centre. The coupled equations of momentum, mass and energy are governed the mathematical model. The governing equations are solved via utilizing the finite difference technique. The outcomes are performed for various combinations of aspect ratios of the solid block, nanoparticles volume fraction and Rayleigh numbers. The outcomes are shown in the form of isotherms, streamlines, and Nusselt numbers. It is concluded that the increment of average Nusselt number is detected when the nanoparticles volume fraction and Rayleigh number increase.